2000
DOI: 10.1034/j.1600-0838.2000.010004211.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heart rate controlled low resistance circuit weight training and endurance training on maximal aerobic power in sedentary adults

Abstract: The effects of a 12-week low resistance circuit weight training (CWT) on cardiovascular and muscular fitness were studied in 90 healthy sedentary adults. The subjects were randomized into three equally fit groups: CWT, Endurance (END) and Control (CON) according to their maximal aerobic power (VO2max). Both training groups exercised for 12 weeks, 3 days a week in sessions of 40 min, with a heart rate (HR) level of 70-80% HRmax. The CWT group trained with air resistance machines. Heart rate was controlled by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 0 publications
3
30
2
10
Order By: Relevance
“…In the long term, 18-month lasting selfadministered endurance training did not eVect isometric strength development as reported by Heinonen et al (1998). In line with nonspeciWc response of endurance exercise on strength was the Wnding of Kaikkonen et al (2000) that circuit strength training improved cardiorespiratory Wtness to the same extent as endurance type exercises when executed at the same HR intensity in 35-50 years old untrained women and men. Whether recovery periods between the training sessions would have had an impact on the eVect of muscle strength, muscle quality, or cardiorespiratory Wtness has not yet been thoroughly investigated.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the long term, 18-month lasting selfadministered endurance training did not eVect isometric strength development as reported by Heinonen et al (1998). In line with nonspeciWc response of endurance exercise on strength was the Wnding of Kaikkonen et al (2000) that circuit strength training improved cardiorespiratory Wtness to the same extent as endurance type exercises when executed at the same HR intensity in 35-50 years old untrained women and men. Whether recovery periods between the training sessions would have had an impact on the eVect of muscle strength, muscle quality, or cardiorespiratory Wtness has not yet been thoroughly investigated.…”
Section: Introductionsupporting
confidence: 82%
“…We hypothesized that in untrained females, the strength training would be as eVective as endurance training regarding muscular strength as reported by Macaluso et al (2003) or in improving CRF as described by Kaikkonen et al (2000).…”
Section: Discussionmentioning
confidence: 98%
“…Un trabajo de Kaikkonen et al (2000), concluyó que los efectos cardiovasculares producidos por un entrenamiento de fuerza en circuito con cargas bajas (20% 1RM) en máquinas de musculación en adultos sanos sedentarios, fueron comparables a un entrenamiento de resistencia, realizando actividades como andar, trotar o pedalear. Los programas de entrenamiento duraron 12 semanas, y tanto la FC como el tiempo de duración del ejercicio fue el mismo para ambos tipos de entrenamiento (40 minutos y entre el 70-80% de la FC máx ).…”
Section: Valores Máximosunclassified
“…Sin embargo, no hay estudios que comparen los efectos del entrenamiento de fuerza en estos dos tipos de condiciones en variables cardiorrespiratorias: consumo de oxígeno máximo (VO 2máx ), umbral anaeróbico, frecuencia cardíaca (FC), ventilación (VE), etc., teniendo en cuenta que algunos estudios demuestran que programas de fuerza tradicionales en personas sedentarias tienen efectos cardiovasculares similares a actividades de resistencia como andar, correr o trotar (Kaikkonen, Yrjämä, Siljander, Byman, & Laukkanen, 2000;Hautala et al, 2006). Otros trabajos documentan que el entrenamiento de fuerza no es estímulo eficaz para la mejora del consumo máximo de oxígeno (VO 2max ) (Hurley et al, 1984;Dudley, 1988), a no ser que sean personas sedentarias o de baja capacidad funcional.…”
Section: Introductionunclassified
“…Wilmore's study [21] protocol was similar to that used in Gettman's study when 30 s of CWT at 40-55% of 1RM was followed by 15 s of rest for 8 weeks. Similarly, Kaikkonen et al [11] showed that circuit weight training with resistance of 20% 1RM with an appropriate HR level had effects comparable to an equal amount of endurance training on the aerobic capacity of sedentary adults. The CWT group trained with air resistance machines for 12 weeks, 3 days a week in sessions of 40 minutes, with a HR level of 70-80% HRmax.…”
Section: Studiesmentioning
confidence: 99%